Cell Analysis on Microfluidics - Lin, Jin-Ming.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2018)
This book presents a detailed overview of the design, formatting, application, and development of microfluidic chips in the context of cell biology research, enumerating each element involved in microfluidics-based cell analysis, discussing its history, status quo, and future prospects, It also offers an extensive review of the research completed in the past decade, including numerous color figures. The individual chapters are based on the respective authors' studies and experiences, providing tips from the frontline to help researchers overcome bottlenecks in their own work. It highlights a number of cutting-edge techniques, such as 3D cell culture, microfluidic droplet technique, and microfluidic chip-mass spectrometry interfaces, offering a first-hand impression of the latest trends in the field and suggesting new research directions. Serving as both an elementary introduction and advanced guidebook, the book interests and inspires scholars and students who are currently studyingmicrofluidics-based cell analysis methods as well as those who wish to do so.
Design and preparation of microfluidic devices -- Recent development of cell analysis on microfluidic -- Cell isolation and recognition with microfluidic device -- Cell culture and observation on microfluidics -- Cell migration with microfluidic chips -- Biomaterial-based microfluidics for cell culture and analysis -- Droplet-based cell analysis on microfluidic -- Single cell analysis on microfluidic -- Microfluidics-mass spectrometry for cell analysis -- Biochemical analysis on microfluidic chips -- Microfluidic cell culture systems for drug research -- Cell metabolite analysis on microfluidic platform -- Microfluidic platforms for bacteria.
Keywords: Analytical chemistry; Cytology; Soft condensed matter; Analytical Chemistry; Cell Biology; Soft and Granular Matter